Hubungan Asupan Protein dan Konsumsi Tanin dengan Kadar Hemoglobin Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis di RS Santo Yusup Bandung - Anastasia Yohana; Yuliati Widiastuti; Asysyfa Riana (Universitas Muhadi Setiabudi, 2026)
Chronic Kidney Disease (CKD) patients undergoing hemodialysis have a high risk of anemia due to decreased hemoglobin levels, one of which is caused by inadequate protein intake and tannin consumption that inhibits iron absorption. This study aims to determine the relationship between protein intake and tannin consumption with hemoglobin levels in CKD patients undergoing hemodialysis at Santo Yusup Hospital, Bandung. The study design was cross-sectional and involved 86 respondents selected using a simple random sampling technique. The variables studied included protein intake, tannin consumption, and hemoglobin levels. Data were collected using a Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) questionnaire and medical records, and analyzed using the chi-square test. The results showed that 50% of respondents had insufficient protein intake, 31.4% consumed tannins frequently, and 56.9% had low hemoglobin levels. The chi-square test showed a significant relationship between protein intake and hemoglobin levels (p=0.000), as well as between tannin consumption and hemoglobin levels (p=0.017). Patients with low protein intake and high tannin consumption are at higher risk of low hemoglobin levels. Appropriate nutritional interventions are needed to improve hemoglobin levels in CKD patients undergoing hemodialysis. Keywords: Chronic Kidney Disease, Hemodialysis, Protein Intake, Tannin Consumption, Hemoglobin